The Prospects and Challenges of Biopolymers for Enhanced Oil Recovery (EOR) - Maudy Pratiwi Novia Matovanni; Muhammad Nur Ikhsanudin; Rizky Ibnufaatih Arvianto; Joko Waluyo; Sperisa Distantina; Mujtahid Kaavessina; Sunu Herwi Pranolo (Equilibrium Journal of Chemical Engineering, 2023)
Abstract. Currently, Enhanced Oil Recovery (EOR) technology is being interested in the Indonesian state as an advanced technology that can recover oil remaining in the reservoir. The discovery of new resources and EOR efforts are predicted to result in increased oil production. This paper provides a review of main types of EOR methods, which are gas injection, thermal injection, and chemical injection; mechanism of polymer flooding; and biopolymer materials for EOR, attention were given to xanthan gum, cellulose, guar gum, and lignin. Polymer flooding is a low-cost chemical injection method with a high rate of success. Polymer flooding has several advantages, including improving oil recovery by minimizing residual oil saturation, decreasing water output from oil well, and requiring less water compared with water flooding. Since the use of polymer flooding in the EOR activities, there is a lot of potential that biopolymers are materials that play a significant role in the application of EOR technology, because environmentally friendly properties and have advantages over synthetic polymers. Biopolymer can be modified to nano materials or grafted with synthetic polymer to improve its properties and stability. It have shear, salinity, and temperature resistance, long-term stability, and large availability, so it making the right choice for applications in oil recovery.Keywords:Enhanced oil recovery, EOR, biopolymer, polymer flood, modification of biopolymer